The vanishing type - Adams, Ellery (Adams, Ellery. Secret, Book, and Scone Society novel, 2022)
When a deputy asks for help with a wedding proposal and a man connected to his future wife is found dead, Nora Pennington and her fellow readers investigate the connection to the woman's past and the secret she is hiding from everyone.